DESAIN PENGELOLAAN RUANG TERBUKA HIJAU DI “KAWASAN SUMBER KOMPLEK PERKANTORAN”, KABUPATEN CIREBON - virna apriliani; kushandajani .; turtiantoro . (Journal of Politic and Government Studies, 2016)
The urban as a civilization and the economy of the public faced with a problem like the degradation of the quality of the environment and over the function of land to be the center of the settlement residents, office complex, the road, shop, and shopping centers. The Cirebon regency start doing mending themselves to the city of green clean, beautiful and eternal through the development and management green open space. The purpose of this research is to analyze an action plan the green open space and described the management green open space at Sumber complex office area of Cirebon regency.The research used in this study is descriptive qualitative which aims to give an idea of a conditional of objectively. The source of data collected in this study is the primary data and secondary data. Primary data obtained through direct observation and interview while secondary data obtained from the reports of the realization of the building of the green open space at Sumber complex office area of Cirebon regency.The results of reserach can be know that an action plan the green open space at Sumber complex office area of Cirebon regency consists of the development of the Sumber city of the forest and city garden. Departmen of Regional Development in Cirebon Country in 2014 has been able to provide a leafy green new with widely 266,3 ha. While the management the green open space at Sumber complex office area of Cirebon regency consisting of the activities watering, turn of the plants, cleaner plants, butchering plants and fertilization plants. As for the management green open space to integrated and sustainable by Departmen of Regional Development in Cirebon Country in 2014 is new reaches 4,28% consisting of park city, tre area of sport, median and island of the road.Recommendation can be given the increas in the capacity Departmen of Regional Development in Cirebon Country and relevant agencies as Departement of Environmental, Departement of Tourism and Departement Farm and Ranch Plantation in Cirebon Country with expanding the reach of and increased scrutiny in management green open space at Sumber complex office area of Cirebon regency.Keyword: green open space, management and action plan